Tiga Tipe Praktik Sosial dan Gaya Visual Pelukis Barat di Bali - Adnyana, I Wayan (Jurnal Kajian Bali (Journal of Bali Studies), 2019)
This article studies the social practices of Western painters in Bali based on Orientalism perspective, a Western style for dominating, restructuring, and having authority over the Orient. The painters who were sampled were those who represented in each wave of arrival: (a) 1930-1940s (Spies, Bonnet, Hofker and Le Mayeur), (b) 1950-1980s (Blanco, Smit and G. Couteau), and (c) 1990-present (Hirst, Sciascia and Bickerton). Three types of social practices were found: (1) consciously decide to dissolve with the interaction of Balinese painters, which further produce visual artistic appropriations between the two parties; (2) make Bali only as their work studios based on various specific considerations, the visual style of the work becomes the dominant discourse—Bali is only a mere object or locus; (3) decide to marry Balinese women, some even become Indonesian citizens, established authority over mini Bali in the families they build, visual styles tended to be Bali portraits.